0036 The Impact of Nighttime Eating: A Randomized Controlled Trial of Daytime vs. Delayed Eating on Weight and Metabolism in Adults of Normal Weight. (12th April 2019) - Goel, Namni; Hopkins, Christina; Ruggieri, Madelyn; Zhang, Zhe; Taylor, Deanne M; Allison, Kelly C
Abstract: Introduction: The timing of eating is a significant contributor to body weight regulation. The effects of a consistent, prolonged delayed eating pattern compared with a daytime pattern on weight and metabolism remain unclear, however, since few highly controlled, rigorous human trials exist. We report on the final dataset of such a controlled trial. Methods: Twelve healthy adults (age: 26.3±3.4y; BMI: 21.9±1.7 kg/m 2 ; 5 females) participated in a randomized cross-over study in free-living conditions. Three meals and two snacks consisting of comparable energy and macronutrient content were provided during two, 8-week counterbalanced phases: 1) daytime (food consumed between 0800h-1900h) and 2) delayed (food consumed between 1200h-2300h). A 2-week washout period occurred between the conditions. Participants were asked to maintain a sleep-wake cycle between 2300h-0900h (verified by wrist actigraphy) and to limit physical activity. Weight, adiposity, energy metabolism, and hormonal markers were assessed during four inpatient visits: 1) baseline; 2) after the first eating condition; 3) after the washout period, before the second eating condition began; and 4) after the second eating condition. Two-way ANOVAs and Cohen's d effect sizes examined changes in anthropometrics and metabolic measures affected by eating schedule (daytime vs. delayed) and time (before vs. after each eating schedule). Results: Weight, the trunk to leg fat ratio, respiratory quotient, and fasting insulin, total cholesterol, and glucose decreased (improved) on the daytime schedule, while fasting triglycerides increased on the delayed schedule (all changes showed medium to large effect sizes; d> 0.5). Actigraphic sleep-wake variables, physical activity and light levels did not differ between eating schedules (p's>0.05). Conclusion: This controlled trial provides the first experimental evidence that an 8-week daytime eating schedule, as compared to an 8-week delayed eating schedule, promotes weight loss and a positive profile for energy metabolism and hormonal markers in healthy adults of normal weight. Thus, nighttime eating contributes to weight gain and metabolic dysfunction independent of calorie intake. Our findings have implications for other eating paradigms including time-restricted feeding. Support (If Any): NIH R21DK100787.